Über den Einfluss von Werkstoffkennwerten auf das Spanbruchverhalten von bleiarmem Messing: About the influence of material properties on the chip breaking behavior of low‐leaded brass. Issue 6 (27th June 2018) - Hofmann, U.; Nobel, C.; Baier, S.; Buchkremer, S.; Döbbeler, B.; Klocke, F.
Translation abstract: Low‐leaded brass materials are gaining in industrial significance due to multiple national and international legislative regulations. Reducing the mass fraction of lead in brass material leads to unfavorable chip forms in machining and an increased chip volume ratio, which is a measure of their bulk volume. Cutting tests show that a certain amount of reduction in lead content can be compensated by adjusting the machining parameters feed and cutting depth. A phenomenological model for the calculation of the chip volume ratio as a function of the lead content and the machining parameters is developed. This work shows that there is no significant correlation between chip volume ratio and standardized material testing procedures such as tensile test, hardness testing or quantitative microstructural analysis.